Progress on the development of a metal salt-assisted ionization source for the mass spectrometric analysis of polymers. Issue 29 (15th July 2022) - Muyizere, Theoneste; Mukiza, Janvier
Abstract : Schematic illustration of development of metal salt-assisted ionization sources-mass spectrometry for soft ionization of polymers. Abstract : The mass spectrometric analysis of polymers has been addressed as a challenging research topic due to poor ionization and complicated analysis using conventional mass spectrometry. The ionization source has demonstrated a promising future in rapid mass spectrometric analysis. Soft ionization techniques, such as electrospray ionization (ESI) and matrix-assisted laser desorption/ionization (MALDI) are the most ionization sources appeared to be a powerful tools for polymer characterization when combined with MS. However, they always need metal salts to be introduced during the ionization protocol for polymers due to the crucial role played by their ions (cations and anions). The current review focuses on the progress in the development of metal ion-assisted-ionization sources for the mass spectrometric analysis of polymers. Different ionization systems are comprehensively reviewed. The application of metal ion-assisted ESI, nanoESI, PSI, and MALDI-MS for polymer sample analyses is systematically discussed. The future research trends and challenges in this cutting-edge research field are summarized. It also aims to provide the current state-of-the-art of metal salts as a platform for ionization systems for the mass spectrometric characterization of polymers and offers the current challenges and perspectives on the promising future to improve analytical performance in this field. Finally, this mini-review provides a comprehensive handbook to researchers from different research backgrounds wishing to work in this area.